A novel type-2 innate lymphoid cell-based immunotherapy for cancer - Saranchova, Iryna; Xia, Clara Wenjing; Besoiu, Stephanie; Finkel, Pablo L.; Ellis, Samantha L. S.; Kari, Suresh; Munro, Lonna; Pfeifer, Cheryl G.; Fazli, Ladan; Gleave, Martin E.; Jefferies, Wilfred A. (Frontiers in Immunology, 2024)
Cell-based cancer immunotherapy has achieved significant advancements, providing a source of hope for cancer patients. Notwithstanding the considerable progress in cell-based immunotherapy, the persistently low response rates and the exorbitant costs associated with their implementation present a formidable challenge in clinical settings. In the landscape of cell-based cancer immunotherapies, an uncharted territory involves Type 2 innate lymphoid cells (ILC2s) and interleukin-33 (IL-33) that promotes ILC2 growth, recognized for their inherent ability to enhance immune responses. Recent discoveries regarding their role in actuating cytolytic T lymphocyte responses, including curbing tumour growth rates and hindering metastasis, have added a new dimension to our understanding of the IL-33/ILC2 axis. These recent insights may hold significant promise for ILC2 cell-based immunotherapy. Nevertheless, the prospect of adoptively transferring ILC2s to confer immune protection against tumours has yet to be investigated. The present study addresses this hypothesis, revealing that ILC2s isolated from the lungs of tumour-bearing mice, and tumour infiltrating ILC2 when adoptively transferred after tumour establishment at a ratio of one ILC2 per sixty tumour cells, leads to an influx of tumour infiltrating CD4+ and CD8+ T lymphocytes as well as tumour infiltrating eosinophils resulting in a remarkable reduction in tumour growth. Moreover, we find that post-adoptive transfer of ILC2s, the number of tumour infiltrating ILC2s is inversely proportional to tumour size. Finally, we find corollaries of the IL-33/ILC2 axis enhancing the infiltration of eosinophils in patients expressing high levels of IL-33 versus those expressing low levels of IL-33 prostate carcinomas that associated with recurrent prostate cancers. Our results underscore the heightened efficacy of adoptively transferred ILC2s compared to alternative approaches, revealing an approximately one hundred fifty-fold superiority on a cell-per-cell basis over CAR T-cells in the specific targeting and elimination of tumors within the same experimental model. Overall, this study demonstrates the functional significance of ILC2s in cancer immunosurveillance and provides the proof of concept of the potential utility of ILC2 cell-based cancer immunotherapies.